Peningkatan Kemampuan Berpikir Kreatif Siswa DalamMemecahkan Masalah Belajar Ips Terpadu MelaluiPendekatan Saintifik Dengan Model PembelajaranProblem Based Learning (PBL) Pada Siswa KelasVIII B MTs N SURAKARTA 1 TAHUN AJARAN 2016/2017 - DWI JAYANTI, ELIN; , Dra. Titik Asmawati, SE, M.Si (2017)
This study aims to improve students' creative thinking by applying a scientific approach to learning model Problem Based Learning. This research is a classroom action research conducted in two cycles. The subjects were teachers who provide action and action recipients are students of class VIII B MTs N Surakarta 1 totaling 38 students. Data collection methods used were interviews, observation, and documentation. Data analysis technique used is the process of data analysis, data presentation, and data verification. The results showed an increase in Creative Thinking Integrated IPS students in learning that can be seen from the indicators, namely: 1) The ability to recognize, understand and respond to a question before the act 21.05%, the first cycle was 68.42%, and at the end of the action on cycle II amounted to 89.47%, 2) the ability to generate many ideas in solving a problem before action 15.78%, the first cycle was 73.68%, and at the end of the action on the second cycle amounted to 94.73%, 3) ability proposed solution or approach to a prior action pemasalahan 23.68%, the first cycle was 63.15%, and at the end of the action in Cycle II amounted to 84.21%, 4) the ability to solve problems detail.sebelum actions 21.05 %, the first cycle was 68.42%, and at the end of the second cycle measures amounted to 86.84%. Thus concluded that the use of scientific approach to learning model Problem Based Learning (PBL) can improve students' creative thinking in solving